Changes in psychophysiological condition of high skilled female wrestlers in the dynamics of the menstrual cycle. - Stelmakh J.J (Kharkov National Pedagogical University, 2012)
The features of functioning of organism of sportswomen are studied in the dynamics of menstrual cycle and the changes of the psychophysiological state of sportswomen are investigational in each of phases of menstrual cycle. In research took part 35 highly skilled sportswomen - fighters in age 18-29 years. The questionnaire of sportswomen is conducted with the purpose of determination of age, sporting qualification, terms and state of flowing of menstrual cycle on the questionnaire of N.V. Svechnikova in modification of L.G. Shakhlina. The results of own researches of the psychophysiological state of sportswomen of high qualification are presented. Recommendations are resulted for trainers on application of pedagogical influences, which are directed on the increase of psychical firmness, overcoming of the physical and emotional loadings of sportswomen in the premenstrual, menstrual and ovarian phases of cycle. It is recommended to pick up the adequate loadings taking into account the phase of menstrual cycle, because of decline of capacity and change in the psychoemotional state of sportswomen.